Emergence of multidrug-resistant E. coli ST8346 isolates carrying three distinct plasmids with NDM-5, KPC-2, and OXA-181 - Ping-Yuan Chen; Yu-Chin Chen; Che-Ming Chiang; Chi-Chung Chen; Chih-Cheng Lai; Chia-Hung Tsai; Chung-Han Ho; Po-Yu Chen; Hung-Jen Tang; Julie Chi Chow; Tu-Hsuan Chang (Elsevier, 2024)
Background: E. coli ST8346 is a unique strain associated with the potential carriage of multiple carbapenemases. Three unique E. coli ST8346 isolates were identified, each concurrently harboring multiple carbapenemases, including blaNDM-5, blaKPC-2, and/or blaOXA-181. This study aimed to characterize the genetic and plasmid structures of these isolates to understand their transmission and resistance mechanisms. Methods: Antibiotic resistance profiles, genetic relatedness, and plasmid structures were determined using antibiotic susceptibility testing, multilocus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE), S1 nuclease PFGE, and long-read sequencing. Results: All the strains were carbapenem resistant. PFGE revealed close genetic relationships among the isolates, despite the lack of geographical or epidemiological connections. blaNDM-5, blaKPC-2, and blaOXA-181 were located on separate plasmids. Plasmids harboring blaNDM-5 showed genetic similarities to blaNDM-5-bearing IncF plasmids in the United Kingdom. The IncA/C plasmids harboring blaKPC-2 had identical sequences resembling a plasmid from a K. pneumoniae strain in Taiwan, except for the blaKPC-2 region, which matched a strain from China, indicating a hybrid plasmid. Conclusion: This study is the first to identify and characterize the coexistence of blaNDM-5, blaKPC-2, and blaOXA-181 in E. coli ST8346 isolates. The spread appears to be due to independent acquisition events. We identified the putative origins of these plasmids and detected a possible recombination event in a novel IncA/C plasmid. These findings emphasize the importance of ongoing surveillance and further investigations.